Safety and efficacy of laryngeal mask airway placement in term of oropharyngeal leak pressure: A comparison between conventional insertion and laryngoscope guided insertion - Ayan Ghorui,; Baisakhi Laha,; Sandip Roy Basunia,; Debasish Saha, (Asian Journal of Medical Sciences, 2025)
Background: The effectiveness of laryngeal mask airway (LMA) through conventional insertion technique versus laryngoscope-guided insertion is a debatable issue. Use of only fiberoptic scoring for assessment has shown conflicting results. A newly presented clinical sign – oropharyngeal leak oropharyngeal leak pressure (OLP) – is showing promise for assessing airway sealing in LMA placement. Aims and Objectives: The present study was undertaken to compare the conventional blind insertion versus laryngoscope-guided insertion of LMA using OLP as the main indicator. Materials and Methods: A prospective randomized comparison was done between two groups (Group C-Conventional LMA insertion and Group L-Laryngoscope guided LMA insertion) numbering 100 patients in total. OLP, first attempt success rate, time taken for insertion, hemodynamic variation, and adverse effects were recorded and compared between the groups. Results: OLP was significantly high in laryngoscope-guided LMA insertion than conventional insertion (22.6±3.59 vs. 17.4±3.53 cm H2O [Mean±Standard deviation]). Time taken for LMA insertion (28.3±5.92 vs. 23.3±5.03 s) and hemodynamic stress response was higher in laryngoscope-guided insertion than conventional insertion. The two methods showed a similar profile of complications. Conclusions: Laryngoscope-guided LMA insertion improves the airway seal pressure over conventional blind LMA insertion with some limitations. We suggest laryngoscope guidance may be a better technique for LMA insertion.